Avaliação do desempenho de rebolo seeded-gel na retificação cilíndrica de bicos injetores em aço 18CrNi8 - Garrido, Raynier Enrique Estrada (2021)
Grinding is a process of special importance in machining of mechanical workpieces with demanding tolerances for precision applications. During grinding most part of the energy consumption is converted into heat, for this reason it is necessary to analyse the process in order to achieve the required geometrical conditions of the workpieces without compromising the mechanical properties of the machined surface. In order to increase the industrial efficiency and productivity new abrasives materials for grinding wheels have been developed as the microcrystalline alumina, for example, which allows decrease the energy consumption and the wheel wear rate. In this context, this research compares the performance alumina microcrystalline grinding wheel with the monocrystalline alumina one in the external cylindrical plunge grinding of 18CrNi8 steel, studying the cutting parameters to ensure an adequate surface integrity with optimal conditions of productivity and efficiency for a highly developed and competitive industry. The analysis is based on the study of the power and specific energy of cutting, thermal damages (burning, rehardening layer, tensile residual stresses, microhardness), surface roughness and final dimensions. This study aims to identify the influence of cutting parameters on mechanical properties, avoiding the thermal damages previously mentioned and achieving at the same time, an adequate surface roughness and dimensional precision. The results showed that with the use of microcrystalline alumina grinding wheels, the power consumption and specific cutting energy decreased by about 25%. There was also a decrease in the microhardness of the workpieces machined with microcrystalline abrasives by approximately 3%. Additionally, it was observed that with the use of microcrystalline alumina, the workpieces presented lower thermal affected layer thicknesses with burning and rehardening. Respect to the residual stresses, the use of microcrystalline alumina resulted in an increase of the compressive residual stresses by approximately 25%.